RISK BEHAVIOR FOR BULIMIA AMONG ADOLESCENTS - Lorenna Mendes Temóteo Brandt; Liege Helena Freitas Fernandes; Amanda Silva Aragão; Thayná Pinto da Costa Luna; Rodrigo Macedo Feliciano; Sheyla Márcia Auad; Alessandro Leite Cavalcanti (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To analyze the risk behavior for bulimia among female adolescents from public and private high schools. Methods: A cross-sectional study with a random sample of 850 female students aged 15-18 years was carried out in a city in northeastern Brazil, using the Bulimic Investigatory Test of Edinburgh (BITE) to assess the risk behavior for bulimia. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) software and the Pearson's chi-square , Fisher's exact and robust Poisson regression tests, adopting the significance level of 5%. Results: Less than half of the sample (42.0%) showed standards of dietary risk and weight control practices; in 1.4% of the sample, bulimia signs were already installed. Fear of gaining weight was reported by 62.8% of the subjects. Risk practices were lower among students from public schools; (Odds Ratio - OR - 0.82; confidence interval of 95% - 95%CI - 0.69-0.97). Among restrictive practices, fasting for a whole day was the most applied (29.9% of the students). Among individuals who were at risk situation, almost half believed to have normal eating habits (prevalence ratio - PR - 0.42; 95%CI 0.36-0.49). Individuals who consider their eating habits normal, who are afraid of gaining weight, those who seek emotional comfort in food and follow strict diets had higher risk for bulimia (p<0.05). Conclusions: The number of female adolescent students with risk behavior practices for bulimia is high, and the frequency of those unaware of this situation is also very high. Risk situations emerge as a collective health problem, and individuals from private schools were more likely to be in this situation.